Tax Compliance as the Result of a Psychological Tax Contract: The Role of Incentives and Responsive Regulation - Lars P. Feld; Bruno S. Frey (Center for Research in Economics, Management and the Arts (CREMA), 2006)
In this paper, we develop the concept of a psychological tax contract that goes beyond the traditional deterrence model and explains tax morale as a complicated interaction between taxpayers and the government. Based on crowding theory, the impact of deterrence and re-wards on tax morale is discussed. As a contractual relationship implies duties and rights for each contract partner, sticking to the fiscal exchange paradigm between citizens and the state increases tax compliance. Citizens are willing to honestly declare income even if they do not receive a full public good equivalent to their tax payments as long as the political process is perceived to be fair and legitimate. At the procedural level, a friendly treatment of taxpayers by the tax office in auditing processes increases tax compliance.
Keywords: H26; H73; D73; D78; 330; Tax Compliance; Positive and Negative Incentives; Responsive Regulation